2023
DOI: 10.3390/ijms241411830
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Potential of Exosomal Cytokines IL-6 and IL-10 in Polytrauma Patients

Abstract: Trauma remains a leading cause of morbidity and mortality. Polytraumatized patients need a precise, early diagnosis to avoid complications such as multiorgan failure or sepsis. Inflammatory cytokines, commonly used for diagnosis, have a short half-life, which limits their efficacy as a diagnostic or prognostic marker. In this study, we hypothesized that cytokines in exosomes could have a longer half-life, and therefore could be used as diagnostic and prognostic markers in polytrauma patients. Plasma samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the present study, we propose the suitability of SEC-isolated EVs for polytrauma research and showed that such EVs could be used in a differential analysis of EV surface epitopes [ 20 , 21 ] and/or a cargo analysis of cytokines [ 22 ] and miRNAs [ 23 ]. It is known that isolation methods can influence the measured total protein content of EVs [ 24 ], as well as the EV-particle number [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we propose the suitability of SEC-isolated EVs for polytrauma research and showed that such EVs could be used in a differential analysis of EV surface epitopes [ 20 , 21 ] and/or a cargo analysis of cytokines [ 22 ] and miRNAs [ 23 ]. It is known that isolation methods can influence the measured total protein content of EVs [ 24 ], as well as the EV-particle number [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to EV isolation, plasma was additionally cleared via 30 min centrifugation at, 16000g (4°C). EVs were isolated from 100 µl of plasma by means of size exclusion chromatography (SEC) (EX03-50, Cell guidance system, Cambridge, UK) as described previously ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, EVs carry biologically active surface proteins (derived from the cell of origin) that may be involved in cell-cell communication and postinjury pathology (16) and could be used for tracking injuryresponding cells. In polytrauma patients, it was shown that circulating EVs were changed in number, size, and cargo content (17)(18)(19) and that cell-specific EVs' surface proteins reflected the injury pattern (20). All the above, together with the fact that EVs can cross the blood-brain barrier (21,22), suggests that EVs might be appropriate candidates as blood biomarkers for assessing the biochemical and molecular status of neurological injury in polytrauma patients (20,23).…”
Section: Introductionmentioning
confidence: 99%
“…This has been documented for interleukin-1β (IL-1β), which can be loaded and transported via exosomes in inflammatory and pyroptotic contexts [62,63]. IL-6, IL-10 and TNFalpha could also be transported in this way, giving these mediators a longer lifespan in body fluids and making again exosomes suitable markers for prognostic and diagnostic [64]. The diversity of exosomal contents also suggests a broad and still poorly understood trafficking between cellular compartments.…”
Section: Exosomes Compositionmentioning
confidence: 99%